In quest of aburra´s valley landscape (2010)
The principal aim of this text is to reveal how an ideal of landscape has been set in Medellín, the second urban area of Colombia, and to seek if this western ideal, founded on visual arts, matches the sight seeing and entertainment generated by a local society. The history of ideal landscape in this context, with pre colonial ancient roots, will show certain differences and tropisms encouraged by the site and its particular history.